Viabilidade de nanopartículas de ouro e prata na desinfestação de explantes visando à micropropagação de plantas - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Obtaining plants from micropropagation techniques is becoming a reality for most known species, which is defined by the cultivation of cells, tissues or plant organs in a nutrient medium and maintaining it in an aseptic, controlled environment. There disinfection of the material to be grown is of paramount importance, there is a variety of disinfection methods already known but are not always efficient, requiring new alternatives, as well as Nanotechnology is an extremely innovative technology and has unique functional properties when compared to metal on a macroscopic scale. There is evidence that gold nanoparticles (AuNPs) and silver (AgNPs) have an antimicrobial character, could be an alternative source in the disinfestation of explants. However, this technique has never been tested in plant micropropagation. This study aimed to test the feasibility of using AgNPs and AuNPs in desifestação explants in the micropropagation of woody plant species. The nanoparticles were prepared by Turkevich method, and characterized using UV-visible, Scanning Electron Microscopy and Atomic Force Microscopy. The sensitivity of bacteria and fungi associated with plants was assessed after confirmation by cell viability assay. Five treatments were tested in the disinfestation of explants Eugenia uniflora L: T1 (control); T2 (AuNPs - 1 h); T3 (AgNPs - 1 h); T4 (AuNPs - 30 min); T5 (AgNPs - 30 min). The results show that the Agrobacterium rhizogenes bacteria are sensitive to silver nanoparticles, followed by confirmation by cell viability assay. With regard to sensitivity to the fungus Fusarium sp, nanoparticles do not show satisfactory results. The explants disinfection E. L. uniflora showed the antimicrobial activity of silver nanoparticles with 40% rate in the elimination of fungi and bacteria; gold nanoparticles decreased by 26.67% in the contamination rate. This study demonstrates for the first time the possible use of AgNPs and AuNPs as methods for disinfection of plant explants. But there is need for greater depth study to standardize time and concentration of the use of nanoparticles as disinfest agent and investigate possible effects of their use in plant cells.
Keywords: Nanopartículas de ouro; Nanopartículas de prata; Desinfestação de explantes; Eugenia uniflora L.; Fusarium sp; Agrobacterium rhizogenes; Gold nanoparticles; Silver nanoparticles; Disinfestation explants; CNPQ::CIENCIAS BIOLOGICAS